Hygrothermal behaviour of a room with different occupancy scenarios. (1st May 2023) - Kaczorek, Dobrosława; Basińska, Małgorzata; Koczyk, Halina
Abstract: The thermal and moisture properties of building partitions and the related possibility of moisture buffering affect the water vapour exchange between the superficial layers of the hygroscopic materials and the indoor environment, which results in energy consumption for different purposes. The paper describes an analysis of the hygrothermal behaviour of a roomunder different occupancy scenarios for four wall finishing variants (variable parameters of thermal conductivity index and diffusion resistance of the applied material). The application of gypsum board and cement-lime plaster was analysed with and without a paint coat. Computer simulations using WUFI Plus were used for the analysis. The application of cement-lime plaster without a top paint coat was shown to reduce fluctuations in the amplitude of indoor relative humidity more than the other solutions. Applying a paint coat to the interior surface of a building partition limits the material's buffering properties, and consequently, the indoor relative humidity amplitude increases. Upon improving thermal efficiency, the decrease in indoor relative humidity was higher for a nursery than for an office space. For the air conditioning dynamic operation mode, it was demonstrated that gypsum board walls with no paint coat could reduce energy demand for dehumidifying systems and increase it for humidifying systems. The painted variants are characterised by a higher total energy consumption for humidification and dehumidification purposes. Highlights: Moisture buffering materials reduce the daily amplitude of the indoor relative humidity. Relative humidity depends on the moisture loads and the thermal needs. The moisture buffering effect reveals significant seasonal fluctuations. Moisture buffering materials do not save energy for heating and cooling purposes. Savings occur in energy consumption for dehumidification and humidification purposes.